2004
DOI: 10.1021/es049915u
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Analytical Approach for Visualizing and Tracking Organic Chemicals in Plants

Abstract: Vegetation plays a key role in the environmental fate of many organic chemicals, from pesticides applied to plants, to the air-vegetation exchange and global cycling of atmospheric organic contaminants. Our ability to locate such compounds in plants has traditionally relied on inferences being made from destructive chemical extraction techniques or methods with potential artifacts. Here, for the first time, two-photon excitation microscopy (TPEM) is coupled with plant autofluorescence to visualize and track tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 25 publications
1
61
0
Order By: Relevance
“…Two-photon excitation microscopy (TPEM) is a technique that enables direct in situ visualization of the movement of compounds that autofluoresce inside living plant tissues and has been pioneered by Wild et al to track the uptake and movement of PAH inside living plant leaves (Wild et al, 2004) and roots (Wild et al, 2005). To further improve our understanding on the influence of mycorrhizal inoculation on plant phenanthrene uptake and translocation, we employed this technique to observe differences between mycorrhizal and non-mycorrhizal lucerne roots in the localization of phenanthrene.…”
Section: Tpem Analysismentioning
confidence: 99%
“…Two-photon excitation microscopy (TPEM) is a technique that enables direct in situ visualization of the movement of compounds that autofluoresce inside living plant tissues and has been pioneered by Wild et al to track the uptake and movement of PAH inside living plant leaves (Wild et al, 2004) and roots (Wild et al, 2005). To further improve our understanding on the influence of mycorrhizal inoculation on plant phenanthrene uptake and translocation, we employed this technique to observe differences between mycorrhizal and non-mycorrhizal lucerne roots in the localization of phenanthrene.…”
Section: Tpem Analysismentioning
confidence: 99%
“…The mechanisms responsible for the PAH transfer to plant tissues primarily include sorption from soil particles, uptake by the roots through transpiration, and absorption through the waxy leaf cuticle or through stomata (Wild et al, 2004;Meudec et al, 2006). Thus, heavy pollution at an e-waste recycling area may result in an elevated uptake of PAHs into vegetables.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, numerous research studies have demonstrated that vegetables grown on PAH-contaminated soils may take up PAHs (Wennrich et al 2002). Several mechanisms including sorption (from soil particles), uptake rate through transpiration, volatilization, and redeposition on plant surfaces are responsible for the PAH transfer from soil ecosystem to plant tissues (Fryer and Collins 2003;Wild et al 2004).…”
Section: Introductionmentioning
confidence: 99%